Development of High Lycopene Edible Film from Gac Aril - Oupathumpanont, Orawan; Buadilok , Natchaya (Burapha Science Journal, 2026)
This research aimed to study develop the eye care food products. By studying the possibility of producing high lycopene edible film from gac aril, optimal formula for producing high lycopene edible film from gac aril, physical properties, chemical properties, mechanical properties, and consumer acceptance of high lycopene edible film products from gac aril. The concepts on the development of eye care food products were for finding guidelines for developing eye care food products and studying the optimal formula. The studied factors are (5%, 10% and 15%) wheat starch content (10%, 20% and 30%) sorbitol and (5%, 10% and 15%) cassava starch. These experiments used factorial in CRD. The results revealed that in the study of the concept on the development of eye care food products, the product most demanded by the consumers was a food in the form of film that can melt in a mouth. The optimum formula for producing synthetic fiber sheets to obtain high lycopene from gac hard tube is formula 8, with ingredients: 100% insulation content, 10% wheat starch, 30% sorbitol and 30% sorbitol. 10% cassava starches were scored for sweetness and overall, The consumer acceptance rated the mouth dissolving preference the most. The mean was 7.80 ± 0.74, followed by the appearance. The mean was 7.76 ± 0.82. The product acceptance level was moderate. The mean value was 3.12 ± 0.41 when providing information on benefits and nutritional value of the product, causing consumers to make a 90.00% purchase decision.